Balloon Dilatation of the Minor Duodenal Papilla Up to 4 mm is Safe in a Porcine Model. Issue 4 (August 2017) - Müller, Philip C.; Steinemann, Daniel C.; Sauer, Peter; Z'graggen, Kaspar; Linke, Georg R.; Müller-Stich, Beat P.
Abstract : Objectives: Balloon dilatation of the minor duodenal papilla is a treatment option for symptomatic pancreas divisum. The histologic effects of balloon dilatation have not yet been evaluated. The aim of this study is to investigate the tolerated extent of dilatation of the minor papilla. Materials and Methods: A dilatation of the minor papilla was performed in freshly explanted pancreas of pigs using biliary balloon dilatators. Three organs were not dilated (control group), in each 8 organs a dilatation of 4, 6, and 8 mm, respectively, was performed. Tissue damage was assessed by microscopic evaluation. Ductal wall disruption and perforation as well as a semiquantitative inflammation score was described and compared. Results: Ductal wall disruption was increased by dilatation of 6 (5/8; P =0.019) and 8 mm (6/8; P =0.006) compared with 4 mm (1/8). Median inflammation score was 0 (0 to 0), 1 (0 to 2), and 1 (0 to 2) for dilatation of 4, 6, and 8 mm, respectively (4 vs. 6 mm, P =0.007; 4 vs. 8 mm, P =0.026). No perforation occurred in the 4 (0/8) and 6 mm (0/8) group, 1 perforation occurred in the 8 mm group (1/8). Conclusions: A dilatation of up to 4 mm seems to be safe. However, dilatation of the minor papilla from 4 mm onwards is increasingly associated with tissue damage. These findings should be considered in endoscopic procedures dilating the minor duodenal papilla.